2018
DOI: 10.1016/j.antiviral.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Subgenomic flaviviral RNAs: What do we know after the first decade of research

Abstract: The common feature of flaviviral infection is the accumulation of abundant virus-derived noncoding RNA, named flaviviral subgenomic RNA (sfRNA) in infected cells. This RNA represents a product of incomplete degradation of viral genomic RNA by the cellular 5'-3' exoribonuclease XRN1 that stalls at the conserved highly structured elements in the 3' untranslated region (UTR). This mechanism of sfRNA generation was discovered a decade ago and since then sfRNA has been a focus of intense research. The ability of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 133 publications
(272 reference statements)
3
123
0
2
Order By: Relevance
“…A partial exonucleolytic digest by Xrn1 is common among flaviviruses, resulting in the generation of subgenomic flavivirus RNA (sfRNA) (reviewed in reference 37). Xrn1 also degrades HCV RNA, which is counteracted by the binding of miR-122 (38)(39)(40). We have further shown previously that miR-122 is capable of functional binding to the internal UTR copy (34).…”
Section: Internal Initiation By Hcv Polymerasementioning
confidence: 55%
“…A partial exonucleolytic digest by Xrn1 is common among flaviviruses, resulting in the generation of subgenomic flavivirus RNA (sfRNA) (reviewed in reference 37). Xrn1 also degrades HCV RNA, which is counteracted by the binding of miR-122 (38)(39)(40). We have further shown previously that miR-122 is capable of functional binding to the internal UTR copy (34).…”
Section: Internal Initiation By Hcv Polymerasementioning
confidence: 55%
“…In this study we have identified and structurally characterized xrRNAs in all genera of Flaviviridae, one of the largest families of RNA viruses, expanding on the known distribution of these RNA structures within Flaviviridae (23). Based on our computational, structural, and biochemical data, we propose that the characteristics of these new xrRNAs require a division of the previously proposed class 1 xrRNA (38) into two distinct subclasses: subclass 1a (comprising MBFV, in particular MVEV, ZIKV, WNV, YFV, etc.…”
Section: Discussionmentioning
confidence: 99%
“…1A) (22). During infection, a subset of flaviviral genomes is targeted to the cellular RNA decay machinery, then processively degraded in a 5′ to 3′ direction by Xrn1, until the enzyme halts at an xrRNA in the 3′ untranslated region (UTR) (19,23). The fold of the xrRNA is sufficient for this function, and no accessory proteins nor chemical modification of the RNA are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sfRNAs have been associated with pathogenic outcomes and cytopathicity during infection (Funk et al 2010;Chang et al 2013;Walker et al 2013;Donald et al 2016;Filomatori et al 2017;Junglen et al 2017). Although their full set of functions remains an active area of investigation (Slonchak and Khromykh 2018) sfRNAs have been shown to bind a number of host proteins (Bidet et al 2014;Schnettler et al 2014;Manokaran et al 2015;Moon et al 2015;Goertz et al 2019;Michalski et al 2019) suggesting they affect several processes during infection including inhibiting the interferon response (Schuessler et al 2012) and suppressing RNAi pathways in insects (Schnettler et al 2012;Schnettler et al 2014;Moon et al 2015). Furthermore, there is evidence that sfRNAs are involved in switching between insect vectors and mammalian hosts (Filomatori et al 2017;de Borba et al 2019), enhancing transmission by mosquitoes (Pompon et al 2017;Yeh and Pompon 2018;Goertz et al 2019;Slonchak et al 2020), and altering the cell's mRNA decay program (Moon et al 2012;Michalski et al 2019).…”
Section: Introductionmentioning
confidence: 99%